Glabridin inhibited the spread of polymyxin-resistant Enterobacterium carrying ICEMmoMP63 - Fu, Jiafang; Liu, Yayu; Wang, Fengtian; Zong, Gongli; Wang, Zhen; Zhong, Chuanqing; Cao, Guangxiang (Frontiers in Microbiology, 2023)
Introduction The role of integrative and conjugative elements (ICEs) in antibiotic resistance in Morganella morganii is unknown. This study aimed to determine whether an ICE identified in the M. morganii genome contributed to the polymyxin resistance. Methods Whole-genome sequencing was performed followed by bioinformatics analyses to identify ICEs and antibiotic resistance genes. Conjugation assays were performed to analyze the transferability of a discovered ICE. A drug transporter encoded on the ICE was heterogeneously expressed in Escherichia coli, minimum inhibitory concentrations of antibiotics were determined, and a traditional Chinese medicine library was screened for potential efflux pump inhibitors. Results An antibiotic resistance-conferring ICE, named ICEMmoMP63, was identified. ICEMmoMP63 was verified to be horizontally transferred among Enterobacteriaceae bacteria. G3577_03020 in ICEMmoMP63 was found to mediate multiple antibiotic resistances, especially polymyxin resistance. However, natural compound glabridin was demonstrated to inhibit polymyxin resistance. Discussion Our findings support the need for monitoring dissemination of ICEMmoMP63 in Enterobacteriaceae bacteria. Combined glabridin and polymyxin may have therapeutic potential for treating infections from multi-drug resistant bacteria carrying ICEMmoMP63.